Carbon emissions embodied in China-Brazil trade: Trends and driving factors. (15th April 2021) - Kim, Tae-Jin; Tromp, Nikolas
Abstract: Understanding the causes of growing carbon transfers between developing countries is likely to be the first step in their mitigation. With this in mind, the current paper uses multi-regional input-output analysis to investigate CO2 emissions and value-added embodied in China-Brazil trade. We propose the use of value-added exports, rather than gross exports, to more accurately estimate the economic benefits of trade. We find enormous increases in both CO2 emissions and value-added embodied in exports for China and Brazil between 2000 and 2014. During this period, China's position as a net CO2 emissions and net value-added exporter vis-à-vis Brazil deepens. Major sources of increasing embodied CO2 exports for China were the basic materials and electricity industries and for Brazil were the basic materials, agriculture and mining industries. Estimates of net carbon intensities reveal advantages for China in electronics and for Brazil in agriculture and mining. Structural decomposition analysis shows that the changing consumption in China and Brazil as well as the changing structure of intermediate exports from China to Brazil were important sources of increasing embodied CO2 emissions. This latter finding was possible due to the method proposed in this paper of decomposing the production structure into the domestic, export and import production structures. In line with the key findings, various implications and emission abatement policies are discussed.